2010
DOI: 10.1177/1024258910364308
|View full text |Cite
|
Sign up to set email alerts
|

Employee-driven innovation in the context of Italian industrial relations: the case of a public hospital

Abstract: This article looks at the role of various forms of participation in experiences of employee-driven innovation in Italy. On the one hand, it analyses the extent to which forms of direct and representative participation have fostered processes of organizational innovation driven by the knowledge and creativity of employees. On the other hand, the article identifies the specific limits of these forms of employee involvement in processes of organizational innovation. Innovative experiences of employee involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The literature suggests that successful groups are heterogeneous, interdisciplinary, presenting cross-hierarchy participants, 11 , 13 , 14 combining formal and informal working methods and communication processes 13 , 17 to work on problem setting and problem solving. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that successful groups are heterogeneous, interdisciplinary, presenting cross-hierarchy participants, 11 , 13 , 14 combining formal and informal working methods and communication processes 13 , 17 to work on problem setting and problem solving. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Project management professionalization, by strong project management processes and instruments, 15 , 19 and support provided by key stakeholders, 12 which prevent process segmentation and providing a clear setting for running and managing meetings, 14 increases project success and therefore hospital innovativeness.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, it could be said, that mode 2b knowledge generation was facilitated by mode 2a knowledge generation in terms of the university-driven intervention. However, the changes take time, like, for example, as reported in the study by Telljohann (2010), where the case is about public hospital workers, who reconstructed their actual work process. The research process even reported duration of five years.…”
Section: An Employeedriven Innovation Processmentioning
confidence: 99%
“…Though the research on employee-driven innovation is rather new, the features and requisites for employee-driven innovation have been studied through various case studies of business organizations (Rocha, 2010;Teglborg-Lefèvre, 2010). In service industries, healthcare service contexts such as hospitals are common research objects (Telljohann, 2010;Castren & Maijanen, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To promote employee-driven innovation, business managers could apply structured approaches such as an incentive system for employees (Teglborg-Lefèvre, 2010) and workshops to gather innovative ideas (Telljohann, 2010). In addition to these mechanisms, some researchers have studied the personal and cultural aspects of employee-driven innovation, such as how the agency of employees toward changing their work practices can affect activities in employee-driven innovation (Billett, 2012, Brandi & Hasse, 2012.…”
Section: Theoretical Backgroundmentioning
confidence: 99%